?SYNTHESIS AND SPECTRAL STUDIES OF MIXED lIGAND COMPLEXES OF SOME AZOPYRAZOLONES (Biological Sciences - PJSIR, 1997)
Working procedure for spectral measurement. In the termary complex system studied the three components has been simplified to a two component system Mn+ and salicylaldehyde azopyrazolone, For the spectrophotometric continous variation method, a set of solutions having the to- tal molar concentration constant 6x 10.3 mol dm' of M'"-sA- azopyrazolone or total molar concentration 6xlO,2 mol dm' of U02 (11)/SNPMP complexes, a blank containing the same concentration of SA and azopyrazolone as in the test solution was made.